Cognitive Ability and Working Memory as Predictors of Reading Comprehension in Elementary School Students - Alfiani Vivi Sutanto; Roy Romey Daulas Mangunsong (Department of Special Education, 2025)
This study examines the relationship between cognitive abilities, working memory, and reading comprehension in elementary school students. Using a cross-sectional analytical model, data were collected from 50 students in grades 3 to 6 using standardized instruments that had been adapted and validated to measure cognitive abilities, working memory, and reading comprehension. The results indicate that both cognitive skills and working memory have a positive relationship with reading comprehension, with working memory emerging as the strongest predictor. These results suggest that students' reading comprehension is closely related to their cognitive processing abilities. This study is limited by the relatively small sample size and the use of a cross-sectional design, which restricts causal conclusions. Nevertheless, these findings have important implications for special education and inclusive education practices, particularly in the context of early identification and intervention for students with diverse learning needs. Improvements in working memory and cognitive functioning can serve as a basis for the design of adaptive teaching strategies and support services in elementary school classrooms.